Siege Warfare in the 21st Century from the Perspective of International Humanitarian Law - Mikos-Skuza, Elżbieta (University of Wroclaw. Faculty of Law, Administration & Economics, 2018)
Professor Karol Wolfke was an expert in many areas of public international law, including the sources of law, and in particular international custom. His flagship publication in this field was recognized and quoted internationally. Therefore it was not surprising that the International Committee of the Red Cross (hereinafter referred to as the ICRC) invited Professor Karol Wolfke to contribute to the completion of the Study on Customary International Humanitarian Law, the purpose of which was to identify customary rules of international humanitarian law applicable in international and non-international armed conflicts. He reviewed some parts of the Study and also advised during experts’ meetings convened in Geneva by the ICRC. Therefore it seems very appropriate to reflect in Professor Wolfke’s commemorative book on a topic proving the important role of customary law in filling gaps in international treaties. The topic that has been chosen – siege warfare – unfortunately belongs to very hot issues in today’s international relations and law. In recent years Aleppo in Syria has become a symbolic example of political and legal controversies about siege tactics in contemporary armed conflicts.
Keywords: oblężenie; działania wojenne; międzynarodowe prawo humanitarne; konflikty zbrojne